2015
DOI: 10.1182/blood-2015-04-537498
|View full text |Cite
|
Sign up to set email alerts
|

Familial predisposition and genetic risk factors for lymphoma

Abstract: Our understanding of familial predisposition to lymphoma (collectively defined as non-Hodgkin lymphoma [NHL], Hodgkin lymphoma [HL], and chronic lymphocytic leukemia [CLL]) outside of rare hereditary syndromes has progressed rapidly during the last decade. First-degree relatives of NHL, HL, and CLL patients have an ∼1.7-fold, 3.1-fold, and 8.5-fold elevated risk of developing NHL, HL, and CLL, respectively. These familial risks are elevated for multiple lymphoma subtypes and do not appear to be confounded by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 86 publications
4
88
0
4
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Primary immunodeficiencies (PID) such as DNA repair defects (Nijmegen breakage syndrome, Ataxia telangiectasia, Bloom syndrome or constitutional mismatch repair deficiency), severe combined immunodeficiencies (SCID), common variable immunodeficiencies (CVID), and immune-osseous dysplasias (Di George syndrome or cartilage hair hypoplasia) have an extraordinary risk of developing leukemia and lymphoma. [5][6][7][8][9][10][11][12][13][14][15][16][17]20,21 Although these patients seem to have an inferior prognosis and an increased risk of treatment-related toxicity and death compared to patients with lymphoid malignancies without a PID, curative therapies including allogeneic stem cell transplantation (allo-SCT) have been repeatedly reported. 5,6,10,11,15,16,22 Systematic data on the spectrum of common and rare pre-existing conditions associated with NHL in children and adolescents are scarce with respect to the type of the pre-existing conditions and the clinical characteristics and outcome of the associated NHL subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Primary immunodeficiencies (PID) such as DNA repair defects (Nijmegen breakage syndrome, Ataxia telangiectasia, Bloom syndrome or constitutional mismatch repair deficiency), severe combined immunodeficiencies (SCID), common variable immunodeficiencies (CVID), and immune-osseous dysplasias (Di George syndrome or cartilage hair hypoplasia) have an extraordinary risk of developing leukemia and lymphoma. [5][6][7][8][9][10][11][12][13][14][15][16][17]20,21 Although these patients seem to have an inferior prognosis and an increased risk of treatment-related toxicity and death compared to patients with lymphoid malignancies without a PID, curative therapies including allogeneic stem cell transplantation (allo-SCT) have been repeatedly reported. 5,6,10,11,15,16,22 Systematic data on the spectrum of common and rare pre-existing conditions associated with NHL in children and adolescents are scarce with respect to the type of the pre-existing conditions and the clinical characteristics and outcome of the associated NHL subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Five year relative survival was 67.5% in 1975 to 87.9% in 2007 [6,7]. Incidence of CLL is higher in individuals with family history of CLL [8] patients with Caucasian ethnicity and agent orange exposure. Clinically, the patients commonly present with asymptomatic peripheral blood lymphocytosis or leukocytosis (predominantly lymphocytosis), lymphadenopathy, hepatosplenomegaly, bone marrow failure, and recurrent infections and often with autoimmune hemolytic anemia or autoimmune thrombocytopenia.…”
Section: What Has Evolved In Our Understanding Of Cll-(now In 2016)mentioning
confidence: 99%
“…Moreover, it was believed that aged neutrophils might migrate poorly to sites of inflammation as their expression of CXCR2, the receptor for several major neutrophil-targeted chemokines, such as CXCL8/interleukin-8, is decreased. 2 The discovery that these "age-wise" cells are the first and dominant subtype of neutrophil to be recruited to the sites of infection sheds new light on efficiency and adaptability of the immune system.…”
Section: Irf4 Bcl2mentioning
confidence: 99%
“…In the absence of infection, where neutrophils are recruited to and die within inflammatory sites, neutrophils in circulation do not die in the bloodstream but rather are eliminated in bone marrow (predominant site), spleen, or liver by specialized macrophages. 2 Recently, it has been shown that the aging of neutrophils is microbiota-driven and depends on Toll-like receptors (TLRs), including TLR-2 and TLR-4,…”
Section: Irf4 Bcl2mentioning
confidence: 99%